Antitumor activity of Coptis chinensis rhizome extract against PANC-1 cells - Jeong, Ji Hye; Lee, Hwa Jin (Archives of Biological Sciences, 2025)
Paper description: Dysregulation of Forkhead box M1 (FoxM1) is associated with poor prognosis and metastasis in pancreatic cancer. Effects of Coptis chinensis rhizome extract and its principal isoquinoline alkaloid berberine on PANC-1 pancreatic cancer cells were investigated by focusing on FoxM1 expression regulation. The extract exhibited potential anti-pancreatic cancer activity, partially attributable to its principal constituent berberine, and was associated with FoxM1 downregulation. Coptis chinensis rhizome extract and berberine, have therapeutic potential against human pancreatic cancer. Abstract: The rhizome of Coptis chinensis is known for its antibacterial, anti-inflammatory, and anticancer activities. This study aimed to investigate the anti-pancreatic cancer activity of C. chinensis rhizome and elucidate the molecular mechanism involved in such activity. The C. chinensis rhizome extract (CRE) significantly inhibited the cell viability of PANC-1 pancreatic cancer cells and arrested the cell cycle at the G0/G1 phase. Western-blot analysis revealed that CRE downregulated the protein level of Forkhead box M1 (FoxM1), an oncogenic transcription factor, and its downstream target proteins such as cyclin D1, c-Myc, and survivin. Berberine was identified as the main component in CRE, effectively reducing cell viability and FoxM1 expression. These findings indicate that CRE and berberine can exert anticancer activity by downregulating FoxM1 expression in pancreatic cancer cells and that berberine may partially contribute to the anti-pancreatic cancer properties of CRE. This study highlights that C. chinensis rhizome extract and its main ingredient, berberine, might have therapeutic potential against pancreatic cancer.